Genetic and miRNA Associations Underlying Beta-Blocker Effects on Bone Mineral Density - Nevola, Kathleen. (Tufts University. Tisch Library., 2021)
Thesis (Ph.D.)--Tufts University, 2021.; Submitted to the Dept. of Cell, Molecular & Developmental Biology.; Advisors: Calvin Vary, and Christine Lary.; Committee: Katherine Motyl, Carol Bult, and Douglas Kiel.; Keywords: Bioinformatics, Cellular biology, and Biology.; Osteoporosis is a debilitating and costly bone disease that causes over 2 million fractures per year in the United States. Recent studies have shown that beta-blocker (BB) users have a higher bone mineral density (BMD) and a lower risk of fracture compared to non-users. The mechanism underlying this association is thought to be due to the suppression of adrenergic signaling in osteoblasts, which leads to increased BMD in rodent models. However, the specific mechanism in humans is uncertain. To investigate potential miRNA-mediated mechanisms and associated genetic polymorphisms, we performed a cross-sectional analysis using data from the Framingham Study's Offspring Cohort, integrating clinical data, genetic data, dual-energy X-ray absorptiometry (DXA) scans, and miRNA and mRNA profiling of whole blood. We found nine miRNAs associated with BB use and BMD using multiple linear regression. In parallel network analyses, we discovered a sub-network associated with BB use and BMD that contained two of these nine miRNAs: miR-19a-3p and miR-186-5p. We also showed that these two miRNAs had significantly higher expression in individuals without incident fracture compared to those with fractures and performed meta-analyses using external datasets. Since miR-19a-3p directly targets the ADRB1 and HDAC4 mRNA transcript, we propose BB use may downregulate ADRB1 or HDAC4 expression in osteoblasts through increased miR-19a-3p expression. We used enrichment analysis of miRNA targets and found potential indirect mechanisms through insulin, estrogen, and parathyroid hormone signaling. We next used sex-stratified linear mixed models and conditional joint analysis and determined 11 genetic polymorphisms that were significantly associated with BMD, mediated by BB use. We determined that the alternative allele of rs12414627, an upstream variant of ADRB1, and rs11124190, an intronic variant of HDAC4, were associated with higher BMD in female BB users. These findings were validated in external studies and found to be significant in meta-analyses across 4 cohorts. These polymorphisms were also associated with bone-related miRNAs in female BB users, from which we hypothesize miRNA-mediated mechanisms associated with these genetic effects. These analyses provide a starting point for delineating the role of miRNAs and genetic polymorphisms on the association between BB use and BMD.